Combined Effects of Telehealth and Modified Constraint-Induced Movement Therapy for Individuals with Chronic Hemiparesis - Mary Ann Smith; Machiko R. Tomita (International Journal of Telerehabilitation)
Telehealth use allows improved access to services and results in potential cost savings. The purpose of this study was to examine the effectiveness of a combined modified Constrained Induced Movement Therapy (mCIMT) program using telehealth and in-person sessions, for participants with higher (Group 1) and lower (Group 2) functional ability of the hemiparetic upper extremity. Using a pre-experimental design with a 6-week intervention, 28 participants were assessed twice on use of upper extremity via subjective and objective measures. For the Motor Activity Log, the amount of use and quality of use were significant for Groups 1 and 2.  Significant improvements were shown on the Wolf Motor Function Test (WMFT), the Fugl-Meyer UE, and the Functional Independence Measure (FIM) for both groups except for the strength subtest on the WMFT and the timed portion for Group 1. Percentages of attendance for telehealth and in-person sessions were also compared. Telehealth sessions had a higher attendance rate (84.5%) than in-person sessions (75.3%) (p=.004). The combined mCIMT program of telerehabilitation and in-person group sessions was effective in improving functional ability after a stroke.